The effects of short-term L-citrulline supplementation on arterial stiffness in prediabetic and healthy adults - Nagel, Jessica (My University, 2019)
Background: Prediabetes is marked by elevated levels of plasma glucose. Chronic hyperglycemia may induce thickening of the arteries, oxidative stress, and endothelial dysfunction, a primary cause for cardiovascular disease. In cold temperatures, exaggerated vascular responses augments the risk for cardiovascular events. L-citrulline may attenuate the exaggerated hemodynamic responses to cold exposure. The purpose of this study was to measure the effects of a 2-week L-citrulline supplementation on hemodynamics at rest and during a cold pressor test (CPT). Methods: Blood pressures, indices of wave reflection (augmented pressure (AP) and augmentation index (AIx)), and arterial stiffness (pulse wave velocity (PWV)) were measured at rest and during a CPT in 16 normal and prediabetic older adults (60-85 yrs). Subjects were randomly assigned to 2 weeks of L-citrulline (6g/day) or placebo supplementation in a double-blind crossover design. Results: No significant changes with either intervention at rest. Central pulse pressure (P =.031) and AP (P =.046) in non-prediabetics and AP (P =.027) and Alx (P =.028) in prediabetics were significantly decreased following L-citrulline supplementation compared with placebo. Conclusions: Although L-citrulline had no effect on resting hemodynamics, supplementation attenuates exaggerated vascular responses during CPT. Therefore, L- citrulline may elicit cardioprotective effects from cold exposure in older adults with and without prediabetes.
Keywords: Dietary supplements; Diabetes; Blood pressure; Kinesiology